1995
DOI: 10.1002/bbpc.199500111
|View full text |Cite
|
Sign up to set email alerts
|

HCN Clusters in Molecular Beams and Cryogenic Matrices

Abstract: Cluster formation of hydrogen cyanide (HCN) was traced by mass spectroscopy in molecular beams and by FTIR spectroscopy in cryogenic matrices in which the clusters were embedded. Both experiments provided evidence for the presence of linear (n ≥ 2) and cyclic structures (n ≥ 3) which were predicted by ab initio calculations as comparably stable. The mass spectra clearly reflect a fundamentally different behaviour of the two types of clusters within the expansion zone: the linear species exhibit the cabability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
13
0
5

Year Published

1996
1996
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 25 publications
(27 reference statements)
2
13
0
5
Order By: Relevance
“…While rotational resolution is available in both the microwave 8,9 and infrared [13][14][15][16] gas phase studies, the broadening associated with the inhomogeneous environment in a cold, solid matrix results in broad vibrational bands that mask the dynamics. 24,25 It is clear from all of this work that the preferred structure of the dimer is linear, with the one HCN hydrogen bonded to the other. As with many other weakly bound complexes, the hydrogen bond is quite floppy in this system.…”
Section: Introductionmentioning
confidence: 84%
“…While rotational resolution is available in both the microwave 8,9 and infrared [13][14][15][16] gas phase studies, the broadening associated with the inhomogeneous environment in a cold, solid matrix results in broad vibrational bands that mask the dynamics. 24,25 It is clear from all of this work that the preferred structure of the dimer is linear, with the one HCN hydrogen bonded to the other. As with many other weakly bound complexes, the hydrogen bond is quite floppy in this system.…”
Section: Introductionmentioning
confidence: 84%
“…In fact, this effect can be considered secondary, since the arrangement of the bulky cations seems to be the primary effect responsible for the size of the cavities, in which the anions are located. For comparison, structural studies of HCN also indicated that HCN forms linear hydrogen‐bonded aggregates in all its phases . For example, there are infinite, parallel, linear H‐bridged chains in HCN crystals .…”
Section: Figurementioning
confidence: 99%
“…on the primitive earth, thus playing an important role in prebiotic synthesis. [8][9][10][11][12][15][16][17] With respect to the latter,c ondensation products of HCN are thought to be key intermediates.H ence,aplethora of theoretical [18][19][20][21][22][23][24][25] and experimental [16,19,20,[26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] studies have been performed on HCN and its clusters (HCN) n in the gas phase (microwave rotational spectroscopy,I R, or matrix IR). These studies indicated that HCN forms linear H-bonded clusters in all its phases.Crystal structure elucidation revealed "infinite" parallel, linear hydrogen-bonded chains, [41] while for the liquid phases, al inear structure with an association state of n = 3w as experimentally derived.…”
mentioning
confidence: 99%